2016
DOI: 10.29333/iejme/338
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of GeoGebra On Third Grade Primary Students’ Academic Achievement in Fractions

Abstract: The aim of this study is to examine the effects of GeoGebra on third grade primary students' academic achievement in fractions concept. This study was conducted with 40 students in two intact classes in Ankara. One of the classes was randomly selected as an experimental group and other for control group. There were 19 students in the experimental group, while 21 students in control group. The matching-only posttestonly control group quasi-experimental design was employed. As a pretest, student's first term mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 4 publications
1
14
0
2
Order By: Relevance
“…The learning process will occur if there is communication between the recipient of the message and the source/channel message through the media. This is in line with the meaning of learning media is a tool that serves to convey the message of learning (Mediawati, 2011), So that the learning by using media becomes more effective (Bulut, Akçakın, Kaya, & Akçakın, 2014;Wibowo, 2013;Ismail, Sugiman and Hendikawati, 2013;Susilana, R., Rullyana, G., Ardiansah., & Wulandari, Y., 2022). Therefore, the learning media as part of the learning system has a role in improving student learning outcomes and teacher factors, teaching materials, methods, and so on.…”
Section: Learning Mediamentioning
confidence: 68%
“…The learning process will occur if there is communication between the recipient of the message and the source/channel message through the media. This is in line with the meaning of learning media is a tool that serves to convey the message of learning (Mediawati, 2011), So that the learning by using media becomes more effective (Bulut, Akçakın, Kaya, & Akçakın, 2014;Wibowo, 2013;Ismail, Sugiman and Hendikawati, 2013;Susilana, R., Rullyana, G., Ardiansah., & Wulandari, Y., 2022). Therefore, the learning media as part of the learning system has a role in improving student learning outcomes and teacher factors, teaching materials, methods, and so on.…”
Section: Learning Mediamentioning
confidence: 68%
“…At least nine studies have been conducted on the impact of mathematics apps on student learning (Bulut et al, 2015;Burns et al, 2012;Kong & Kwok, 2005;Moyer-Packenham & Suh, 2012;Nurmi & Jaakkola, 2006;Reimer & Moyer, 2005;Riconscente, 2013;Thambi & Eu, 2013;Zhang et al, 2015). All studies used a pre-and post-test, quasi-experimental design to examine the impact of practice-based, game-based or constructive apps.…”
Section: Learning Performance With Mathematics Appsmentioning
confidence: 99%
“…By visualizing, it becomes possible to improve the calculus learning process by involving students in problem-solving, modeling concepts, and solving open-ended problems [19]. Consequently, they are able to understand the calculus concept comprehensively [20].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have reported that GeoGebra mathematical software is capable of improving the mathematics learning process by involving problem-solving, modeling mathematical concepts and solving open-ended problems. Therefore, it enables students to understand mathematical concepts in a comprehensive manner [19,20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation